Mind your space - Lee, Yun Xuan (Nanyang Technological University, 2023)
Mind Your Space is an investigation of the complex implications of online deception. The exploration of this spatial experience provides a better understanding of the cause and effects of deception, delving deep into the psychological and social motivations behind the ever-evolving nature of deceit.